Compressors : how to achieve high reliability & availability - Bloch, Heinz P., 1933-; Geitner, Fred K., ....- (New York : McGraw-Hill, 2012)
Coverage includes: -Compression principles and internal labyrinths -Selection factors for process compressors -Operation characteristics of turbocompressors -Wet and dry gas seals -Bearings, stability, and vibration guidance -Lube and seal oil systems -Impellers and rotors -Compressor maintenance and surveillance -Inspection and repair of rotors -Machinery quality assessment (MQA) -Failure analysis and troubleshooting -Reciprocating compressor operation, control, maintenance, and rebuilding -Maintenance and operations interfaces -Reciprocating compressor monitoring and surveillance -Training competent compressor engineers
Includes bibliographical references and index.
Keywords: Compressors -- Maintenance and repair; Compressors -- Performance